Determination of optimal drug dose and light dose index to achieve minimally invasive focal ablation of localised prostate cancer using WST11‐vascular‐targeted photodynamic (VTP) therapy. (21st April 2015) - Moore, Caroline M.; Azzouzi, Abel‐Rahmene; Barret, Eric; Villers, Arnauld; Muir, Gordon H.; Barber, Neil J.; Bott, Simon; Trachtenberg, John; Arumainayagam, Nimalan; Gaillac, Bertrand; Allen, Clare; Schertz, Avigdor; et al.
Abstract : Objective: To determine the optimal drug and light dose for prostate ablation using WST11 (TOOKAD® Soluble) for vascular‐targeted photodynamic (VTP) therapy in men with low‐risk prostate cancer. Patients and Methods: In all, 42 men with low‐risk prostate cancer were enrolled in the study but two who underwent anaesthesia for the procedure did not receive the drug or light dose. Thus, 40 men received a single dose of 2, 4 or 6 mg/kg WST11 activated by 200 J/cm light at 753 nm. WST11 was given as a 10‐min intravenous infusion. The light dose was delivered using cylindrical diffusing fibres within hollow plastic needles positioned in the prostate using transrectal ultrasonography (TRUS) guidance and a brachytherapy template. Magnetic resonance imaging (MRI) was used to assess treatment effect at 7 days, with assessment of urinary function (International Prostate Symptom Score [IPSS]), sexual function (International Index of Erectile Function [IIEF]) and adverse events at 7 days, 1, 3 and 6 months after VTP. TRUS‐guided biopsies were taken at 6 months. Results: In all, 39 of the 40 treated men completed the follow‐up. The Day‐7 MRI showed maximal treatment effect (95% of the planned treatment volume) in men who had a WST11 dose of 4 mg/kg, light dose of 200 J/cm and light density index (LDI) of >1. In the 12 men treated with these parameters, the negative biopsy rate was 10/12 (83%) at 6 months, compared with 10/26 (45%) for the men who had either a different drug dose (10 men) or an LDI of <1 (16). Transient urinary symptoms were seen in most of the men, with no significant difference in IPSS score between baseline and 6 months after VTP. IIEF scores were not significantly different between baseline and 6 months after VTP. Conclusion: Treatment with 4 mg/kg TOOKAD Soluble activated by 753 nm light at a dose of 200 J/cm and an LDI of >1 resulted in treatment effect in 95% of the planned treatment volume and a negative biopsy rate at 6 months of 10/12 men (83%).